2018
DOI: 10.1097/md.0000000000009811
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and vitamin D3 in children with growth hormone deficiency

Abstract: Vitamin D may prevent dental caries. To date, no attempts have been made to examine the correlation between the incidence of caries and the concentrations of vitamin D in children with pituitary growth hormone deficiency.The study observed patients of the Department of Endocrinology and Diabetology of the University Paediatric Hospital of the Medical University of Lublin treated with human recombinant growth hormone for pituitary growth hormone deficiency (GHD). The study was conducted between October 2014 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…Vitamin D 3 levels were analysed in four categories according to the range of concentrations (0–10 ng/mL—severe deficit, 11–20 ng/mL—deficit, 21–30 ng/mL—suboptimal concentration, and above 30 ng/mL—normal concentration). Vitamin D 3 concentrations in particular categories (0–10 ng/mL, 11–20 ng/mL, 21–30 ng/mL, and above 30 ng/mL) varied in a statistically significant manner (Pearson's Chi 2 test = 8.90; df = 3; p = 0.031; Figure 1) [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D 3 levels were analysed in four categories according to the range of concentrations (0–10 ng/mL—severe deficit, 11–20 ng/mL—deficit, 21–30 ng/mL—suboptimal concentration, and above 30 ng/mL—normal concentration). Vitamin D 3 concentrations in particular categories (0–10 ng/mL, 11–20 ng/mL, 21–30 ng/mL, and above 30 ng/mL) varied in a statistically significant manner (Pearson's Chi 2 test = 8.90; df = 3; p = 0.031; Figure 1) [18].…”
Section: Resultsmentioning
confidence: 99%
“…In subjects from rural regions, we demonstrated a significant influence of vitamin D 3 concentration in specific categories on mean DMFT index. Mean DMFT index decreased with an increase in vitamin D 3 level (categories) (univariate analysis of variance ANOVA F = 2.95; p = 0.049; Table 2) [18]. On the other hand, in a population of patients from urban areas, there was no statistically significant impact of vitamin D 3 concentration in the analysed concentration categories on mean DMFT index (univariate analysis of variance ANOVA F = 0.44; p = 0.73).…”
Section: Resultsmentioning
confidence: 99%
“…Another study found a direct correlation of serum vitamin D levels in children, 6-17 years of age. The authors found a drop in DMFT of 0.66 at each 10 ng/ml increase of vitamin D [60]. Regarding the correlation of vitamin C and the occurrence of caries lesions there are controversial results.…”
Section: Hard Dental Pathological Processesmentioning
confidence: 99%
“…Vitamin D treatment in children or in mothers during pregnancy were associated to caries incidence or experience in five papers [60,61,[64][65][66]. Two cross-sectional studies [67,71] were done associating vitamin C intake and caries (levels and experience) and erosion in children.…”
Section: Hard Dental Pathological Processesmentioning
confidence: 99%
“…Most of the studies about vitamin D and GHD in children were conducted between 2014 and 2018 on the one hand or before 1997 on the other [ 72 84 ].…”
Section: Vitamin D Metabolism and Gh In Clinical Pediatric Studiesmentioning
confidence: 99%